(untitled) (Fiep Bulletin - online, 2025)
Introduction: Autism Spectrum Disorder is associated with a chronic neurodevelopmental condition that can have an adverse impact on essential areas of the individual’s life, including personal, family, social, professional and educational aspects, which makes it necessary to establish measures that ensure their full inclusion and integral development of these individuals. Objective: The general objective of this study was to verify whether the effective Physical Education teachers of the municipal network in the urban area of Floriano-PI use pedagogical strategies that include students with ASD in their classes. Methods: The methodological approach used is a qualitative research of exploratory descriptive nature, where a questionnaire was used as a data collection instrument, applied to the effective physical education teachers of the municipal network of Floriano - PI. Results: The table presents the strategies used to minimize and/or overcome the difficulties encountered in Physical Education classes, categorized by the different profiles of participants. Conclusion: It is concluded that, despite the challenges, it is possible to promote the effective inclusion of students with ASD in Physical Education classes through well-planned and executed pedagogical practices, along with effective public policies that guarantee resources and continuous support for the inclusion of students with ASD